2021
DOI: 10.3390/polym13020281
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between SBR Compounds Filled with In-Situ and Ex-Situ Silanized Silica

Abstract: The main advantages of the use of silica instead of carbon black in rubber compounds are based on the use of a silane coupling agent. The use of a coupling agent to modify the silica surface improves the compatibility between the silica and the rubber. There are two different possibilities of modifying the silica surface by silane: ex-situ and in-situ. The present work studies the differences between these processes and how they affect the in-rubber properties of silica filled SBR compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…The difference between pure cyclohexane's freezing temperatures and the solvent's freezing temperature trapped in the rubber compounds may be estimated by comparing the transition temperature values of a confined and a free solvent. 28 The mesh size of the polymer network determines this parameter. The mesh size shrinks as more crosslinks join the polymer chains, and the solvent is trapped in a tighter network, preventing the crystallization of the polymer.…”
Section: Determination Of Hetrogenity Of Elastomer Crosslinks By Solv...mentioning
confidence: 99%
“…The difference between pure cyclohexane's freezing temperatures and the solvent's freezing temperature trapped in the rubber compounds may be estimated by comparing the transition temperature values of a confined and a free solvent. 28 The mesh size of the polymer network determines this parameter. The mesh size shrinks as more crosslinks join the polymer chains, and the solvent is trapped in a tighter network, preventing the crystallization of the polymer.…”
Section: Determination Of Hetrogenity Of Elastomer Crosslinks By Solv...mentioning
confidence: 99%
“…From the FE-SEM micrographs (Figure 4), it is found that all vegetable oils used in this work give similar degree of filler dispersion. Compared with NTO, both MO and NO give smaller size of silica agglomerates and, thus, provide better silica dispersion which leads to the significant improvements in the mechanical and dynamic properties [27][28][29][30].…”
Section: Effect Of Oils On Morphology and Storage Modulusmentioning
confidence: 99%
“…The SEM image of MTES-SiO 2 /EUG/SBR showed that after SiO 2 was modified by MTES, MTES covalently bonded with the silanol groups on SiO 2 . Therefore, the steric hindrance effect on the surface of SiO 2 was improved, and the agglomeration of SiO 2 was reduced [ 46 ], thus, the particle size of SiO 2 dispersed in the material matrix was reduced and the dispersion was significantly improved. The SEM image of SiO 2 /EEUG/EUG/SBR showed that adding EEUG to the matrix also significantly improved the dispersion of SiO 2 .…”
Section: Resultsmentioning
confidence: 99%